Level of knowledge of the process of nursing care (PAE) in caring for the spiritual health of nurses working in critical units of the Hipólito Unanue National Hospital, Lima 2010. - Díaz Orihuela, María Magdalena (2019)
Objective: To determine the level of knowledge about Nursing Care Process (SAP) in the care of the spiritualhealth that owns the nurse working in critical units: Surgery, Emergency and ICU Hospital Hipólito Unanue“, Lima, 2010. Methods: The study was non-experimental design, quantitative approach, descriptive cross.The sample consisted of 40 nurses working in critical units Hipolito Unanue Hospital, determined by randomprobability sampling. For data collection instrument used questionnaire to measure the level of knowledge ofnurses on the care PAE spiritual health, which was developed by the researchers. The instrument was subjected toexpert judgment and test Cronbach Alpha reliability (0.73). The analysis and interpretation of data was performedusing the statistical package SPSS v. 15. Results: The results obtained in the level of knowledge about the carePAE spiritual health were: 57.5% shows a poor level of knowledge, a regular level 27.5%, 12.5% a solid leveland only 2.5% an excellent level, this indicates that the majority of surveyed nurses have poor knowledge levelabout PAE in spiritual care. Conclusion: Most of the nurses know the scientific basis of PAE on spiritual healthcare, this being a constraint to provide nursing care holistically.